The schooling of people with intellectual disabilities in Brazil: From institutionalization to policies of inclusion - Pletsch, Marcia Denise (Education Policy Analysis Archives, 2014)
This article discusses the schooling of people with intellectual disabilities in Brazil during 1973-2013. This study analyzed federal documents and data from ethnographic studies conducted in municipalities of the state of Rio de Janeiro. Data from the study were then compared with statistical data and trends presented in the scientific literature. This article focuses primarily on three dimensions. The first dimension is the historical dispute over the locus of schooling for people with intellectual disabilities, between segregationist perspectives advanced by philanthropic-private initiatives and inclusive perspectives advanced by the public sector (increasingly focused on principles of inclusion since the 1990s). The second dimension refers to the lack of clear guidelines about the curricular practices to be developed by school systems to ensure the development of students, especially those considered severely intellectually disabled. The third dimension analyzes problems of pedagogical support, particularly in Specialized Educational Services (AEE), as current federal law requires. The results call attention to historically-constructed contradictions in the arena of political disputes in the country and the fragility of the public system in providing conditions for the identification and promotion of educational practices promoting learning and development for people with intellectual disabilities.